Comparison of FFR with iFR and QFR in assessment of intermediate coronary artery disease in patients with severe aortic stenosis. (25th November 2020) - Kleczynski, P; Dziewierz, A; Rzeszutko, L; Dudek, D; Legutko, J
Abstract: Background: The functional assessment of coronary artery disease (CAD) in patients with severe aortic stenosis (AS) has been barely examined so far, and the best strategy to physiologically investigate the relevance of coronary stenosis in this specific setting of patients remains undetermined. The aim of the study is to compare the diagnostic performance of instantaneous wave-free ratio (iFR), quantitative flow ratio (QFR) and fractional flow reserve (FFR) in patients with severe AS. Methods: The functional significance of 416 coronary lesions was investigated with iFR, FFR and QFR measurements in 221 AS patients. The iFR-FFR and QFR-FFR diagnostic agreement has been tested using the conventional 0.80 FFR cut-off. Results: Mean value of FFR was 0.85±0.07; iFR – 0.90±0.04; QFR – 0.84±0.07. The correlation between iFR and FFR was good (r=0.83, p<0.001) and QFR and FFR was goot too (r=0.77, p<0.001), as well as the area under the curve at ROC curve analysis 0, 995 (0, 983 to 0, 999, p<0.001) for iFR and 0, 988 (0, 972 to 0, 996, p<0.001) for QFR. However, using the standard iFR 0.89 and QFR 0.8 threshold, the diagnostic accuracy of iFR was 100% sensitivity and 90.26% specificity and for QFR – 100% and 92.21%, respectively. According to ROC analysis, the best iFR cut-off in predicting FFR ≤0.8 was 0.88 (J=0.94), the best QFR cut-off value was 0.80 (J=0.92). Conclusions: In the presence of severe AS, iFR and QFR had good agreement with FFR values for assessment of borderline coronary lesions. However, iFR threshold for predicting FFR below 0.8 may be different from a standard value of 0.89. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Science Centre